1528. Rates of Peripheral Blood Culture Contamination in an Urban Children’s Hospital - Tam, Derek (Open Forum Infect Dis, 2019)
BACKGROUND: Positive peripheral blood culture results are essential in guiding antimicrobial therapy in patients with bacteremia. However, false-positive results may frequently pose diagnostic issues in interpreting the test. These results can lead to increased costs and patient harm through the administration of unnecessary antibiotics and prolongation of hospital stay. The maximum acceptable contamination rate for peripheral blood cultures as suggested by the College of American Pathologists is 3%. METHODS: We initiated a longitudinal quality improvement project to monitor peripheral blood contamination rates at our children’s hospital in Brooklyn, NY. We reviewed positive blood culture results on a monthly basis and assessed whether they represented true infections vs. contamination based on review of patient charts. Residents and nurses in the pediatric emergency department (ED), neonatal intensive care unit (NICU), pediatric intensive care unit (PICU), inpatient unit, and newborn nursery were educated on proper skin sterilization techniques using video demonstration; the importance of avoiding palpating the venipuncture site after sterilization and the importance of cleaning the port on the blood culture bottle were reinforced. RESULTS: The pediatric ED and the PICU had the highest contamination rates in 2018 at 4.38% and 3.82%, respectively. The newborn nursery had the lowest contamination rate, at 0%. The NICU and pediatric inpatient units had contamination rates that met the goal as well, at 1.25% and 0.72%, respectively. CONCLUSION: The departments in need of targeted interventions are the pediatric ED and the PICU, both of which had contamination rates greater than the 3% goal rate set for our project. Future interventions currently being considered include re-education of nursing and resident staff as well as the creation of equipment bundles to facilitate adequate skin preparation prior to venipuncture. [Image: see text] DISCLOSURES: All authors: No reported disclosures.